Pengembangan Aplikasi Kalkulator Multifungsi Menggunakan Flutter Framework - Febri Listiana Harahap; Richi Andrianto; Pebriana Panggabean; Putri Hanafia; Panusunan Panusunan; Mulia Garang (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
Flutter is an open-source user interface (UI) software development kit (SDK) created by Google, designed for building natively compiled applications for mobile, web, and desktop platforms from a single codebase. It employs the Dart programming language and provides a rich set of pre-built widgets, offering developers the flexibility to craft visually appealing and interactive user interfaces. This paper presents an overview of the Flutter framework, discussing its core features, architecture, and benefits. Flutter's